Proposals for adaptation to new economic change through the promotion and selection of holiday villages in Romania - Florentina MIU (Buletin ştiinţific: Universitatea din Piteşti. Seria Ştiinţe Economice)
Any settlement that is chosen to promote rural tourism is based on the following fundamental components: the centre of the village where most households are concentrated and which expresses the economic functions of the village; its outskirts (work area) is the land beyond the center of the village that supports all agricultural occupations, craft, trade, tourism; the population is represented by demographic indicators: birth rate, mortality, natural growth, morbidity, density. Identification and selection criteria for tourist villages are the potential of rhe natural environment composed of natural elements with great appeal, variety of landscapes (mountain, Alpine hills, lakes, delta), ambient aesthetic beauty (slopes, canyons, gorges, caves), wildlife hunting, forests; accessibility is dependent on geographical location in the territory and the main communication routes that connect with the nearest urban centers. Also, the presence of cultural and ethnographic elements are the most attractive ones for tourists; demographic and economic potential have an important role in the development of rural tourism in a village through: supporting agricultural and non-agricultural occupations, transmission of traditions and customs from generation to generation; preserving environmental quality has become an important milestone for the selection and preservation of rural tourist elements.